Cloaks and torsos: image recognition, ethnography and male initiation events in the rock art of the Western Cape. Issue 4 (2nd October 2021) - Parkington, John; Paterson, Andrew
ABSTRACT: Ethnographers and anthropologists have noted that no examples of group male initiation rituals have been recorded among the southern San, although they are known to have taken place further north in Angola, Botswana and Namibia. A detailed rock painting in the southwestern Cape Cederberg, South Africa, is composed in such a way that we argue that it is evidence that 'initiation camps' for young men did also take place in the Cape and were recorded in painted form. Of critical importance to the understanding of the imagery is the relationship between male hunter, the eland as quintessential prey animal and the transformation of the skin of the eland torso into a worn cloak. We suggest that conventional depictions of cloaks, highlighting that transformation, were used to identify initiated figures whereas naked figures were to be understood as initiates or uninitiated. All human figures in this composition are, we submit, men by sex, by gender or by both. Under discussion is the recognition of imagery and the role of ethnographic evidence in such recognitions.